Photonic radiofrequency receiver utilizing a phase modulator and a tunable single sideband optoelectronic oscillator. Issue 9 (4th June 2019) - Xiao, Kang; Jin, Xiaofeng; Shen, Xiaoqing; Cong, Bo; Jin, Xiangdong; Yu, Xianbin; Zheng, Shilie; Zhang, Xianmin
Abstract: A photonic radiofrequency (RF) receiver utilizing a phase modulator (PM) and a tunable single sideband (SSB) optoelectronic oscillator (OEO) is proposed and experimentally demonstrated. In this scheme, the RF signal to be detected is modulated on the PM in one optical path, while a local oscillation (LO) signal is optically generated by the SSB OEO in the other optical path. After combining two paths of optical signals via an optical coupler, an immediate frequency (IF) signal is obtained by photonic RF downconversion in a photodetector (PD). Through scanning the LO signal and monitoring the IF signal simultaneously, the input unknown RF signal can be detected. In the experiment, the RF tones with the operating frequency from 8.1 to 12.1 GHz are successfully detected. The minimum detectable RF power at 10.1 GHz is −84.6 dBm, and the spurious free dynamic range of the photonic RF receiver measured is about 73.8 dB/Hz 2/3 .